Pengembangan Aplikasi Manajemen Event Berbasis Web (Studi Kasus: Fakultas Ilmu Administrasi Universitas Brawijaya Malang) - Hendro Febrian Bachri; Bayu Priyambadha; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Events can be defined as activities that are held to celebrate the important things throughout human life both individually and in groups (Noor, 2013). Faculty of Administrative Sciences, University of Brawijaya (FIA UB) is really active in organizing events such as seminars, workshops and competitions. There is an event proposal submission procedure for holding an event in FIA UB. The event proposal submission procedure is different and it depends on who is the event organizer, what resources are required and the where the event will be held. There are some problems that arise in the process of event proposal submission in FIA UB. From the event organizers perspective, they don't know the status of the submission of the event proposals that they have submitted, they also don't know the status of the venue's availability and many of event organizer do not know the flow of the event submission. From perspective of the General and Equipment Subdivision, the checking of venue's availability and recording of venue's reservation that are still performed manually in files is less efficient and time-consuming. So, the author have a solution to make an application called Event Management application. This Event Management application will be implemented using Node.js, Express.js framework and SemanticUI. The testing conducted using unit, validation and browser compatibility testing methods. In unit testing, all of independent paths tested and all of them are valid. The validation testing also shows result 100% valid. While browser compatibility testing shows that this application can be run without missing functionality in Microsoft Edge, Safari, Google Chrome, Firefox and Opera.